The Effect of Startup Pre-surgery Consultation UnitsonWaiting Time before Surgery and Cancellation of Surgery: A Case Study at Farabi Hospital - Seyed Jamalaldin Tabibi; Mohammad Reza Maleki; Jamil Sadeghifar; Reyhaneh Sharifi (Shahid Sadoughi University of Medical Sciences, 2019)
Background: Patient preparation process for surgery is one of the strategic control points in hospitals, which can improve the patient satisfaction and increase the quality of provided services. This study aimed to determine the impact of pre-surgery consultation unit startup on waiting time before surgery and cancellation of surgery. Methods: This cross-sectional and analytical study was conducted in an Eye Hospital in Tehran. The study population included patients hospitalized for cataract surgery at Farabi Hospital in Tehran City, Iran. Data were collected using a researcher-made questionnaire containing information about the participants' gender, age, waiting time, cancellation of surgery, and length of stay. Data were analyzed by SPSS18 using Mann-Whitney and Chi-Square tests. Results: Pre-surgery consultation unit startup was able to significantly reduce the patient waiting time before surgery (P-value < 0.001). No significant change was observed in cancellation rate and length of stay after the pre-surgery consultation unit startup (P-value > 0.05). Conclusion: Considering the reduction of patients' waiting time as one of the key indicators in eye surgery, preoperative consultation process and other effective processes should be improved to maximize benefits of establishing a preoperative consultation unit at Farabi Hospital.